Gravitational redshift explained as a Doppler Effect in uniformly accelerated frames - Sfarti, A. (Journal of AppliedMath, 2024)
Einstein predicted a change in the energy of photons in the proximity of a gravitational field, the change being directly proportional with the distance from the gravitational source. In the following, we will present an approach to the experiment relying on the Einstein Equivalence Principle and on the recently derived expressions of the Doppler Effect for uniformly accelerated motion of the source and the receiver. We will conclude with a chapter on the numerical limits of applicability of the described method.